The indultados of tescua: criminal rebellion and judicial reckoning during the war of the supremes (2012)
In 1841 the public of Bogota followed the trial of 22 prisoners charged with the crime of rebellion during the War of the Supremes. Captured while serving as officers at the battle of Tescua, the accused claimed they had been forced to serve in the rebel army. This excuse was ignored and 21 of the defendants were sentenced to death, only to be spared by decrees of indulto in the following months. This article examines the logic behind such judicial reckoning, the narrative strategies employed by the accused in their defense, and the meaning of clemency in the early republic.